2018
DOI: 10.1002/maco.201810252
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and corrosion inhibition properties of pyridine‐2‐aldehyde‐2‐quinolylhydrazone for Q235 steel in acid medium: Electrochemical, thermodynamic, and surface studies

Abstract: A new organic compound pyridine‐2‐aldehyde‐2‐quinolylhydrazone (PAQ) was synthesized and its structure was characterized by 1H NMR and FTIR spectroscopy. The inhibition effect of PAQ on the Q235 steel corrosion was investigated with potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM)/energy dispersive X‐ray spectroscopy (EDX), and scanning electrochemical microscope (SECM). The inhibition mechanism was further studied in view of the effect of inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…As described in Figure , the polarization curves obtained by each test system are almost identical in shape, which shows that the addition of CMT (Figure a), ECT (Figure b), Tween-80 (Figure c), or CMT/ECT + Tween-80 (Figure a,b) does not lead to changes in the electrochemical corrosion reaction mechanism of mild steel in hydrochloric acid solution. Moreover, β a and β c changed little with the use of the above inhibitors, which also indicated that these adsorptive inhibitors acted by simple blocking the active reaction sites on the steel surface without effecting the corrosion mechanism. , …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…As described in Figure , the polarization curves obtained by each test system are almost identical in shape, which shows that the addition of CMT (Figure a), ECT (Figure b), Tween-80 (Figure c), or CMT/ECT + Tween-80 (Figure a,b) does not lead to changes in the electrochemical corrosion reaction mechanism of mild steel in hydrochloric acid solution. Moreover, β a and β c changed little with the use of the above inhibitors, which also indicated that these adsorptive inhibitors acted by simple blocking the active reaction sites on the steel surface without effecting the corrosion mechanism. , …”
Section: Resultsmentioning
confidence: 93%
“…Moreover, β a and β c changed little with the use of the above inhibitors, which also indicated that these adsorptive inhibitors acted by simple blocking the active reaction sites on the steel surface without effecting the corrosion mechanism. 27,28 Moreover, it is noteworthy from Figure 6 and Table 4 that the values of E corr after adding CMT/ECT shifted to negative with respect to the blank, and both the cathode and anode reactions were strongly suppressed, while the inhibition effect on the cathode was stronger. This observation suggested that CMT/ECT inhibitors were mixed-type inhibitors that predominantly restrained the cathode process, and the mode of action was "negative catalytic effect".…”
Section: Potentiodynamic Polarizationmentioning
confidence: 94%
“…For this study, the best model was obtained to be the Langmuir isotherm. The Langmuir adsorption isotherm is defined by the following equation: italicCitalicθ=1Kads0.25em+0.25emitalicC,where K ads is the equilibrium constant for the adsorption–desorption process, C is the inhibitor concentration, and θ is the metal surface coverage. Figure illustrates the Langmuir isotherm plot ( C /θ vs. C ).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the ph constant at around 100 Hz and also peak broad wing is maximum with increasing TBAB concentration due to TBAB molecules adsorbed the surface of the specimen. Their adsorption is proportional to the inhibitor concentrations [35][36] which for mild steel in 1NHCl solution. The results from covenant with weight loss method.…”
Section: Adsorption Isothermmentioning
confidence: 99%